-2(x-2)-3x=-6+5x

Simple and best practice solution for -2(x-2)-3x=-6+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-2)-3x=-6+5x equation:



-2(x-2)-3x=-6+5x
We move all terms to the left:
-2(x-2)-3x-(-6+5x)=0
We add all the numbers together, and all the variables
-2(x-2)-3x-(5x-6)=0
We add all the numbers together, and all the variables
-3x-2(x-2)-(5x-6)=0
We multiply parentheses
-3x-2x-(5x-6)+4=0
We get rid of parentheses
-3x-2x-5x+6+4=0
We add all the numbers together, and all the variables
-10x+10=0
We move all terms containing x to the left, all other terms to the right
-10x=-10
x=-10/-10
x=1

See similar equations:

| 5(3/2x+6)=90 | | 2x+10=6x+40 | | 2x+7+(9/(2x-1))=0 | | 6+c/2=4 | | 5n+n=6n | | 7x+4=5x=20 | | -6(x-6)+10x=30 | | X+14+x-17+6x-5=180 | | B÷2+5=2b | | 1/3j+9=0 | | X+14+x-17=6x-5 | | 6x-5+x+14+x-17=180 | | 6x-5+x+14=x-17 | | 180=2x+5x+3x+50 | | x=2x+5x+3x+50 | | 7x-10+2x+5+2x+9=180 | | 55x-25=10x+20 | | -2=9x+12 | | 3x-5x+88x=4x+18 | | 14x-10x=3x | | -6x-2=3x+12 | | 4x-(75-x)=125 | | 4^x-8=1/1024 | | r=7/6r | | 3x+2x=7x-x | | 40+5x+x=180 | | 6a-3/2=9/2 | | 4/7x+2=22 | | 10x+80=160 | | 3(n+2)=8 | | 4+5b-2b^2=5 | | 0=3x-20- |

Equations solver categories